Elevated neurofibrillary tau levels emerge with subthreshold Aβ accumulation in Down syndrome. (31st December 2021) - Zammit, Matthew D; DiFilippo, Alexandra H; Tullis, Tyler; McVea, Andrew K; Tudorascu, Dana L; Laymon, Charles M; Cohen, Ann D; Zaman, Shahid; Ances, Beau M.; Hartley, Sigan L; Johnson, Sterling C.; Stone, Charles K; et al.
Abstract: Background: Adults with Down syndrome (DS) are genetically predisposed to Alzheimer's disease (AD) and accumulate beta‐amyloid plaques (Aβ) early in life. The aim of this study was to evaluate neurofibrillary tau deposition in DS between groups of Aβ negative (A‐) and subthreshold Aβ accumulators (subthreshold A+). Method: A total of 130 adults with DS (age=36.5 [6.77] years) and 40 healthy, non‐DS sibling controls (43.2 [12.6] years) underwent T1w‐MRI, [C‐11]PiB and [F‐18]AV‐1451 PET scans. MRI images were processed using FreeSurfer v5.3.0 to generate ROI masks encompassing the Braak staging of tau pathology. PiB and AV‐1451 SUVr images were generated using a cerebellar gray matter reference region. Global Aβ burden was calculated using the amyloid load metric (AβL ). Of the 130 DS adults, N=26 were classified as subthreshold A+ (13.3 < AβL < 20), and the remaining 104 were classified as A‐ (AβL < 13.3). AV‐1451 images were averaged for each group, and the difference was taken to generate a ΔSUVr image. Regional tau was assessed using AV‐1451 SUVr Z‐scores relative to the sibling control group. Partial volume correction was performed on AV‐1451 SUVrs in the Braak I‐II regions using the geometric transfer matrix method. Braak regional SUVr Z‐scores were then compared across the two groups using Student's t‐tests while adjusting for imaging site. The analysis was then repeated using an age‐matched sample of A‐ (N=68) and subthreshold A+ (N=26) DS. Result: The SUVr difference image revealed higher AV‐1451 uptake in Braak regions I‐III for the subthreshold A+ group (Figure 1). Student's t‐tests revealed significantly higher AV‐1451 uptake in Braak regions I‐III for the subthreshold A+ group (Table 1). No difference in AV‐1451 uptake was observed between groups in Braak regions IV‐VI (Table 1). Higher AV‐1451 uptake in Braak regions I‐III was also observed in the subthreshold A+ group when compared to the age‐matched A‐ group (Table 2). Conclusion: These results show that subthreshold Aβ in DS is accompanied by elevated tau in the early Braak stage regions. These findings indicate that there is a short latency between the onset of Aβ and the spread of neurofibrillary tau in DS.